PERLINDUNGAN HUKUM TERHADAP NOTARIS/PPAT ATAS PERBUATAN MELAWAN HUKUM YANG DILAKUKAN OLEH KARYAWAN NOTARIS/PPAT - Muhammad Ridho Rifani; Achmad Faishal; Saprudin (Collegium Studiosum Journal, 2023)
The purpose of conducting this research is to analyze the legal protection of a Notary/PPAT whose responsibility is as a recipient of a client's document entrusted with the purpose of making a Deed to be disabled or negligent for acts against the law committed by Notary/PPAT employees, as well as to analyze the legal consequences for the Notary/PPAT for the delivery of client's documents to parties other than the client carried out by employees without the knowledge of the Notary/PPAT. According to the results of the study, one of the obligations of a notary based on the Notary Office Act is to safeguard the interests of the parties involved in legal actions. One of them is in terms of keeping an item entrusted to a Notary/PPAT for the process of making a deed. This obligation also applies to the employee of the Notary concerned, and the obligation to maintain the client's documents applies until the position of the Notary ends (retirement). However, in this case the Notary/PPAT employee does not carry out these obligations properly, the Notary employee submits the client's documents to a party other than the client without the Notary/PPAT's knowledge. carried out by employees. Even though in practice employees are trusted by the Notary/PPAT to assist in keeping the client's documents, however, in the case of an unlawful act committed by the employee, the Notary is responsible for the unlawful act committed by the employee as the employer. This shows the need for legal protection for Notaries/PPATs which is very detrimental to the Notary and is closely related to the good name of his profession as a Notary and his colleagues.